1999
DOI: 10.1159/000013523
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Hepatitis C Viremia in Renal Allograft Recipients

Abstract: In an attempt to study the impact of HCV viremia on renal transplant clinical course and outcome, we prospectively followed 133 HBsAg-negative end stage renal disease (ESRD) patients, in whom HCV-RNA-PCR results were available, from the pre- to post-transplant period. Eighty (60%) ESRD patients tested PCR-positive, of these, 12 (15%) were anti-HCV negative by second generation ELISA. The viremic patients had a longer time on dialysis (p < 0.001), received more blood units (p < 0.001) and had a higher frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…We and others have reported a high prevalence (16%) of HCV antibodies among healthy blood donors and a much higher prevalence (38%) of HCV antibodies among patients with glomerulopathy (10,11). It is known that the prevalence of HCV is higher among HD patients than the general population (12) with an even higher prevalence -as high as 60% -of hepatitis C viremia reported among our renal transplant recipients (13).…”
Section: Discussionmentioning
confidence: 55%
“…We and others have reported a high prevalence (16%) of HCV antibodies among healthy blood donors and a much higher prevalence (38%) of HCV antibodies among patients with glomerulopathy (10,11). It is known that the prevalence of HCV is higher among HD patients than the general population (12) with an even higher prevalence -as high as 60% -of hepatitis C viremia reported among our renal transplant recipients (13).…”
Section: Discussionmentioning
confidence: 55%
“…The prevalences of HBV infection were 6.2% in 1994, 4 HBVϩ patients had been significantly longer on dialysis than negative patients (67.4 Ϯ 54.9 vs 35.3 Ϯ 32.9 months; P Ͻ .001). The acute rejection rate seemed to be higher among HBVϩ (48.1%) than negative patients (32.9%); however, the difference was not significant.…”
Section: Resultsmentioning
confidence: 96%
“…Some studies have reported an increased risk of death among patients who test positive for HCV antibody and HBsAg prior to kidney transplantation, 1,2 whereas others have reported no effect on patient or graft survivals. 3,4 The aim of this study was to evaluate the impact of HCV and HBV infections on renal transplant patients and their grafts, at a single center. This study also sought to analyze the evolution of prevalence of these infections over the last years in Portugal.…”
mentioning
confidence: 99%
“…Muitos destes estudos publicados não têm demonstrado, de forma inequívoca, um efeito deletério desta infecção viral em pacientes transplantados renais a curto ou médio prazo 3,8,9 . No entanto, em estudos com maior tempo de seguimento tem-se demonstrado pior sobrevida dos pacientes anti-HCV positivos quando comparados aos anti-HCV negativos 10,11,12 .…”
Section: Discussionunclassified